Feature-based characterisation of laser powder bed fusion surfaces - Senin, Nicola; Thompson, Adam; Leach, Richard K. (2017)
A novel algorithmic pipeline for the automated identification and dimensional/geometric characterisation of topographic formations of interest (surface features) is proposed, specifically aimed at the investigation of signature features left by laser powder bed fusion of metallic surfaces. Unmelted and partially-melted particles, as well as spatter formations and weld tracks, are automatically identified and extracted from topography datasets obtained via state-of-the-art areal topography measurement instruments, and then characterised in terms of their size and shape properties. Feature -based characterisation approaches, such as the one proposed in this work, allow for development of new solutions for the study of advanced manufacturing processes through the investigation of their surface fingerprint.